Advanced computer aided manufacturing applications for turning processes - Tan, Beng Hwang (2016)
The application of computer technology have influenced numerous development in turning manufacturing process. Generally, a detailed variables have to be defined including cutting parameters, process parameters and machining operations. Nevertheless, process planning needed skilled process planners, longer process planning time spent and has low level of dependability. This paper aims to develop an user interface program controller where in order to support the decision making with large volume of data and to optimise the process planning task, the integration between intelligent systems for example Computer Aided Design (CAD), Computer Aided Process Planning (CAPP) and Computer Aided Manufacturing (CAM) have strengthened the relation between design and manufacturing stages. Through the integration of these intelligent systems, application of graphical user interface (GUI) for automated process planning in turning machining is developed to provide an effective machining process. The main purpose of the developed user interface program is to assist the process planning tasks in turning machining for construct machining program with minimum time and minimalize the need of skilled user in the process. Moreover, the graphical user interface (GUI) is able to improve the process planning in turning operations by integrating decision making tools and optimize process parameters such as spindle speed, depth of cut and cutting feed rate based on operation features with minimum human intervention and embed substantial levels of automation in the planning stage.